APPLICATION OF INTERACTIVE QR CODE BASED ONLINE SHOPPING SYSTEM - Mr. Rajratan Pandit Banegaon; Mr. Lobo L.M.R.J (International Journal of Innovations in Engineering Research and Technology, 2022)
In this research work, the authors are nominating a solution for busy life style of the people to convert their waiting time into the shopping time without going to any shopping mall. A ‘QR’ code is used to provide this above-mentioned solution due to various advantages over other systems. Combination of Image Processing with Data Mining to provide encoding and decoding data into QR for providing various services has been done. Authors conclude that the data mining technology can generate new business opportunities by providing the capabilities, automated prediction of trends and behaviors, and automated discovery of previously unknown patterns.